Efficacy of a topical formulation combining fipronil, moxidectin, and praziquantel (Banni3) in controlling flea infestation in cats - Campos, Diefrey Ribeiro; Marré, Ester Oliozi; Cruz, Breno Cayeiro; Cruz, Gessica Ariane de Melo; Michels, Milenni Garcia; Gatto, Igor Renan Honorato; Almeida, Ferdinando Nielsen de; Rosa, Dandara Quelho; Correia, Thais Ribeiro; Scott, Fabio Barbour (Frontiers in Veterinary Science, 2025)
Ctenocephalides felis felis is the most common parasitic insect worldwide, responsible for transmitting pathogenic agents to cats. The aim of this study was to evaluate the efficacy of a novel formulation containing fipronil 12.5%, moxidectin 0.83%, and praziquantel 8.3%, in the treatment of cats, both artificially as well as naturally infested with C. felis felis. For the controlled study, 14 cats were divided into a control group that received no treatment and a treated group that received the investigational product (Banni3 – 12.5% fipronil + 0.83% moxidectin + 8.3% praziquantel – Ourofino Saúde Animal Ltda.). Each animal was artificially infested 48 h before each evaluation with 100 fleas. Evaluations to determine efficacy were based on the average count of live fleas found in the control and treated groups and were carried out nine times after treatment for 56 days. For the field study, 110 indoor cats, naturally infested with C. felis felis, were included. These animals were divided into the positive control group, which received a topical formulation of 10% fipronil, and the treated group which received the investigational product. The efficacy evaluations were based on the average number of live fleas found pre-treatment and post-treatment and were carried out on days four times after treatment 30 days. For artificially infested cats, there was a statistically significant difference (P < 0.05) between the mean flea counts of the negative control and treated groups, and the efficacy was 100% from the second day up to 14 days after treatment, and then 99.3%, 97.8%, 96.0%, 92.0% and 92.5%, respectively, 21, 30, 35, 42 and 49 days after treatment. For cats that had natural infestations, the effectiveness was 98.6%, 99.7%, 98.7% and 97.3% on days 7, 14, 21 and 30 after treatment, respectively. There was no statistically significant difference (P > 0.05) when comparing flea counts between the treated group and positive control, but there were statistically significant differences (P < 0.05) in the pre- and post-treatment evaluations. A topical treatment with Banni3, administered as a single dose, is proven safe and effective for controlling C. felis felis in artificially and naturally infested cats.